Melody and Words in a Song: Issues Regarding Song Teaching from Preschool through 4th Grade - Pereira, Ana Isabel (2016)
To our knowledge, songs are the musical resource most used with preschool and primary school-aged children.Acknowledging that the linguistic and musical development in these ages is at a critical stage, we propose to analyse the interaction between melody and words in memory for songs. Several studies in the field of perception and musical cognition are discussed in terms of the influence of both components in a song identity and recognition. Assuming different ways of perceiving and encoding songs, we extend this discussion to the influence of teaching songs with words and without words in encoding and vocal performance of children. Furthermore, we compare two different procedures for teaching songs based on the results of several studies. We also place the importance of using songs without words within Music Learning Theory developed by Edwin Gordon. Finally, according to the studies discussed, we point out relevant aspects to be considered when teaching songs and for further researches.